Design of the local spin polarization at the organic–ferromagnetic interface - Atodiresei, Nicolae; Brede, Jens; Lazić, Predrag; Caciuc, Vasile; Hoffmann, Germar; Wiesendanger, Roland; Blügel, Stefan (Physical review letters, 2010)
By means of ab initio calculations and spin-polarized scanning tunneling microscopy experiments the creation of a complex energy dependent magnetic structure with a tailored spin-polarized interface is demonstrated. We show this novel effect by adsorbing organic molecules containing π(p(z)) electrons onto a magnetic surface. The hybridization of the out-of-plane p(z) atomic-type orbitals with the d states of the metal leads to the inversion of the spin polarization at the organic site due to a p(z)-d Zener exchange-type mechanism. As a key result, we demonstrate the possibility to selectively and efficiently inject spin-up and spin-down electrons from a ferromagnetic-organic interface, an effect which can be exploited in future spintronic devices.